Response of Integrated Weed Management and Planting Patterns on Seed Productivity of Pea - PARMINDER SINGH; J.S. KANWAR; KULBIR SINGH (Seed Research, 2026)
The field experiment was conducted in split plot design with two planting methods i.e. Bed Planting (60 cm and two rows in each beds) and flat planting with 30 cms row to row spacing in main plot and six weed control treatments namely Pendimethalin 0.75 kg. a.i./ha, Pendimethalin 0.75 kg. a.i./ha+ hand weeding 30 days after sowing, Trifluralin 1.25 kg a.i./ha, Trifluralin 0.75 kg a.i./ha + hand weeding 30 days after sowing, hand weeding at 30 days interval and unweeded in sub plot in pea cv. Matar Ageta-6. The application of Pendimethalin 0.50 kg. a.i./ha + hand weeding and Trifluralin 0.75 kg a.i./ha + hand weeding were found suitable for the effective weed control and for increasing seed yield. Bed planting system is the best for getting maximum seed production (17.7 q/ha) due to its congenial environment for root development and ultimately helping better crop stand, hence resulting in more productivity.